Improvemento Financial Activity Management by the Information System - A. Gareeva, Gulnara; R. Grigoreva, Diana (International Journal of Engineering and Technology, 2018)
A special place in financial management is financial planning, which is the process of developing a system of financial plans and indicators to ensure the development of the company with the necessary financial resources and increase the efficiency of its activities in the forthcoming period.In this study, the analysis and reengineering of the business processes of the enterprise "KZTAiA", in accordance with the concepts of process-task management technology. As a result, the main business processes are identified and the links of their tasks are revealed. The paper considers the project of the subsystem "Financial management", which presents the organizational and logical essence of the solution of its tasks, internal and external information links.The task "Formation of the budget for spending money" of the subsystem "Financial management" was also developed and the business case for the development and implementation of the task was made. Total development costs - 41198 rubles, Labor saving â€“ 5831,83 rubles. Based on the methodology for estimating net cash flow, a simple payback period of the project is found - 10.3 months and the discounted payback period of the project is 10.7 months. The introduction of this task gives a managerial effect and a synergetic effect, which is related to the use of the results of solving this problem in solving other problems.The object of the research is the enterprise KZTAiA - Kama Plant of Brake Apparatus and Aggregates - an enterprise for the production of special tools and technological equipment, fire trucks and other special equipment, equipment repair, supply of standard and special tools.Â